Homesick and Migration Effect - Lienggar Rahadiantino; Banu Prasetya (IPTEK Journal of Proceedings Series, 2019)
Migration plays an important role in development, especially in the labor economy. This paper reflects the factors that influence structural migration patterns in Indonesia using data from the 2014 Indonesian Family Life Survey (IFLS). We use a probit regression model to determine whether migration without partners and the amount of income affect migration again. by involving control variables, such as the number of migration trips, the distance of the migration location from the area of origin, and area of origin. The results show that a person decides to return to his home area when migrating himself. Migration without other household members causes a person to tend to lose his home. In addition, someone will migrate again when the amount of income received is lower than expected. Sacrificed utility costs cannot cover the burden of dependence on the area of origin. in addition, migrants from Java will choose to migrate again rather than settle.